The Fed and the new monetary consensus: The Case for Rate Hikes, Part Two - L. Randall Wray (Levy Economics Institute of Bard College, 2004)
The most charitable interpretation of the Federal Reserve's recent interest rate hikes is that they appear to have been premature. A convincing array of data on payrolls, employment-to-population ratios, and other labor market indicators show that the current recovery has not yet attained the degree of labor market tightness that was common in previous recoveries, and therefore that the threat of inflation is minimal. Hence, the Fed, in raising rates, was unnecessarily jeopardizing the economy's weak recovery. In this new brief, we learn about the flaws in the Fed's thinking that have led to its frequent policy mistakes. Author L. Randall Wray traces several strands of current central bank thinking back to their roots in the Fed's internal discussions in the mid-1990s. Transcripts of these discussions have recently been released, a development that has yielded some disturbing and telling insights about the way in which monetary policy is formed.
Keywords: 330; Geldpolitik; Zinspolitik; Geldpolitisches Ziel; Konjunkturpolitik; USA